Effect of core strength training on the badminton player's performance: a systematic review & meta-analysis - Ma, Shuzhen; Soh, Kim Geok; Japar, Salimah; Liu, Chunqing; Luo, Shengyao; Mai, Yiqiang; Wang, Xinzhi; Zhai, Mengze (Public Library of Science, 2024)
Background Core strength training (CST) has been shown to improve performance in several sports disciplines. CST is recognized as one of the crucial elements that enhance athletic performance, particularly impacting badminton skills. Despite its popularity as a strength training method among badminton players, there is a lack of comprehensive studies examining the effectiveness of CST on the performance of these athletes. Objective This study aims to ascertain CST's effects on badminton players' performance. Method This study followed PRISMA principles and conducted comprehensive searches in wellknown academic databases (SCOPUS, Pubmed, CNKI, Web of Science, Core Collection, and EBSCOhost) up to August 2023. The inclusive criteria were established using the PICOS framework. Following their inclusion based on PICOS criteria, the selected studies underwent literature review and meta-analysis. The methodological quality of the assessments was evaluated using Cochrane Collaboration's risk of bias tools bias risk tools and recommendations for a graded assessment, development, and evaluation. Results The analysis included participants aged 10-19 years from 13 studies of moderate quality, totaling 208 individuals. The CST intervention s lasted between 4 to 16 weeks, with a frequency of 1 to 4 sessions per week and each session lasting 20 to 120 minutes. Sample sizes across these studies ranged from 8 to 34 participants. According to the meta-analysis, CST significantly influenced badminton performance, particularly in areas of explosive power (ES = 0.03 P = 0.04), front-court skill (ES = 2.53, P = 0.003), and back-court skill (ES = 2.33, P = 0.002). Conclusion CST enhances badminton players' fitness (strength, power, balance, and stability), in situ (front/back-court) skills, and movement position hitting. However, its effects on speed, endurance, agility, flexibility, and coordination are unclear, revealing a research gap. The precise benefits of CST, especially on flexibility and specific hitting skills (smashes, clears, drives, net shots, crosscourt, push, and lift shots), need more investigation. Additionally, research on CST's impact on female athletes is significantly lacking.